ANALYSIS OF THE INFLUENCE OF DIGITAL MARKETING ON CONSUMER PURCHASING DECISIONS IN THE DIGITAL ECONOMY ERA - Loso Judijanto; I Putu Gede Didik Widiarta; Luckhy Natalia Anastasye Lotte (Adisam Publisher, 2025)
This research aims to analyze the influence of digital marketing on consumer purchasing decisions in the digital economy era through a literature review approach. The development of information technology has fundamentally changed the marketing landscape, where consumers are now increasingly active and selective in making purchasing decisions. This study was carried out using the library research method, by examining various scientific sources such as journals, books and research reports published in the last five to ten years. The analysis results show that digital marketing elements such as social media marketing, content marketing, and influencer marketing have a significant and consistent influence on the purchasing decision stages, especially in creating awareness, building interest, and encouraging action. Apart from that, this research also found that the influence of digital marketing is strengthened by factors such as consumer trust, brand loyalty, and the quality of digital content which act as mediators and moderators. The implications of these findings indicate that an effective digital marketing strategy must prioritize an integrated, relevant and consumer experience-oriented approach. Thus, strategic use of digital marketing can be the key to winning business competition in an increasingly competitive digital economy era.